An Assessment of School Plant Management and Covid-19 Mitigation for Quality Assurance: Experience From Kwara State - Oluwatoyin, Fashiku Christopher; Abiola, Yusuf Abubakar; Baba, Ayoku Oba (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The study assessed school plant management and COVID-19 mitigation for quality assurance in Kwara State public primary schools. In the study, a descriptive survey research design was used. In Kwara State public primary schools, 390 teachers were chosen using a multistage sampling technique. The study used a self-designed and validated questionnaire titled "SFMCQ" to collect data, and the index's reliability coefficient was 0.82. The results showed that the level of school plant management for COVID-19 mitigation in Kwara State public primary schools was moderate (55.9%); the government's measures to mitigate the spread of the COVID-19 pandemic are the provision of stationed washing hand basins (76.5%); training and re-training support for human resources (61.3%); hand sanitizers (58.2%); school fumigation (52.2%); and the level of compliance with the government's measures A significant relationship existed between school plant management and COVID-19 mitigation in the schools (r =0.921, df = 389, P < 0.05). The study concluded that school plant management moderately enhanced COVID-19 pandemic mitigation for quality assurance in the schools. As a result, as nice as the government's measures are, there is a need for the government to develop a more robust contingency plan for COVID-19 mitigation and other emergencies that may disrupt the education system in the near future.